Isolation of Endophytic Fungi from Trichoma of the Simpei Fern (Cibotium barometz (L.) J. Sm) and Phosphate Solubilizing Activity Test - Nia Ramadhanti; Dezi Handayani; Azwir Anhar; Irdawati (Jurnal Serambi Biologi, 2023)
The problem that is often faced by farmers in West Sumatra is the decreasing level of soil fertility which has an impact on crop production due to a lack of phosphate uptake by plants. The problem of phosphate availability can be overcome by utilizing phosphate solubilizing fungi (CPF) because they can be used as biofertilizers. CPF is usually isolated from the soil or rhizosphere, but this fungus is not necessarily compatible with the host plant, so the isolation of endophytic fungi, especially indigenous fungi, is better because it can provide phosphate. CPF can be isolated from plant tissues such as trichomes. The aim of this study was to isolate endophytic fungi from chimpanzee fern trichomes and test their phosphate solubilizing activity. Samples were obtained from Nagari Aka Barayun, Harau District, Fifty Cities District, West Sumatra. Isolation of fungi using Potato Dextrose Agar (PDA) medium, phosphate solvent activity test using Pikovskaya medium. The results showed that 5 isolates of endophytic fungi were successfully isolated from chimpanzee fern trichomes with different macroscopic morphologies: spherical shape, various colors, cotton-like texture, smooth surface. Phosphate solubilizing activity test showed that only ETK 4 isolate had phosphate solubilizing activity with the highest IKF of 0.7.